2003
DOI: 10.1016/s0045-7825(03)00385-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach of three-dimensional hybrid grid methodology: Part 1. Grid generation

Abstract: We propose a novel approach of three-dimensional hybrid grid methodology, the DRAGON grid method in the three-dimensional space. The DRAGON grid is created by means of a Direct Replacement of Arbitrary Grid Overlapping by Nonstructured grid, and is structured-grid dominated with unstructured grids in small regions. The DRAGON grid scheme is an adaptation to the Chimera thinking. It is capable of preserving the advantageous features of both the structured and unstructured grids, and eliminates/minimizes their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 42 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…In the two rows of near-boundary cells of each of the overlapping or overset grids, the parameters are determined at linear interpolation [15,16] in the manner, as done in [13] . In [15] , it is shown that this approach is equivalent to the application of adaptive unstructured grids, but its computational resources are substantially less, i.e., it is more efficient.…”
Section: Cfd Codes Computation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the two rows of near-boundary cells of each of the overlapping or overset grids, the parameters are determined at linear interpolation [15,16] in the manner, as done in [13] . In [15] , it is shown that this approach is equivalent to the application of adaptive unstructured grids, but its computational resources are substantially less, i.e., it is more efficient.…”
Section: Cfd Codes Computation Methodologymentioning
confidence: 99%
“…Fully unstructured grids are poorly adapted to condense mesh nodes in the vicinity of walls; the computational accuracy of these grids according to high-order schemes is lower than that according to structured grids. At the same time, it should be noted that some interesting tasks of aeromechanics are characterized by the presence of multiply connected computational subdomains, for example, flow around the profile with vortex cells [4,5] , with trailing-edge flaps, and leading-edge flaps [12,13] , flow interactions with a cylinder in a perforated housing when air from a high-pressure zone flows into a low-pressure zone in the wake [14] . In the case of complex flow boundary configurations, the use of single-block (with one matrix) structured grids runs into difficulties; therefore, multiblock overlapping grids have been long used.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of the Chimera method is to generate independent meshes for the components present in the computational domain (e.g., fuselage, airfoil, flap, and slap) and to couple them via a coupling strategy in order to obtain a global solution. The appealing characteristics of the Chimera method has enabled many applications, summarized in the following: Simplified mesh generation . At the time when mesh generators could not handle complex geometries, the Chimera method was proposed as an alternative.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, it has been suggested to first fill an axis-aligned Cartesian mesh in the far field of viscous walls and then connect the boundary layer mesh and the Cartesian mesh with a few transition layers of unstructured elements [12][13][14][15].…”
mentioning
confidence: 99%